Motivations, Quality, and Loyalty: Keys to Sustainable Adventure Tourism in Natural Destinations - Orden-Mejía, Miguel (2025)
This study examines the key factors that influence tourists’ perceptions of destination quality and loyalty in the context of adventure tourism in Santa Elena, Ecuador, an emerging destination in Latin America. A quantitative approach was used, with data collected through an online questionnaire completed by 318 participants. Structural equation modeling was conducted using SmartPLS 4 to examine the relationships between motivational constructs (intellectual curiosity, health assurance, stress relief, physical condition, and social connection), perceived destination quality, and loyalty. The findings reveal that health assurance (β = 0.395, p < 0.001), stress relief (β = 0.417, p < 0.001), and intellectual curiosity (β = 0.143, p = 0.010) significantly influence perceived destination quality, while social connection and physical condition did not show significant effects. Moreover, perceived destination quality strongly predicts tourist loyalty (β = 0.634, p < 0.001). The model explains 63.5% of the variance in destination quality and 48.1% of that in loyalty. These results highlight the importance of post-pandemic health concerns, emotional well-being, and intellectual engagement as drivers of satisfaction and loyalty in adventure tourism. While existing research has largely focused on motivations and quality perceptions in adventure tourism within developed regions, studies in post-pandemic settings across Latin America—especially using validated structural models—remain scarce. This study also contributes to filling a gap in the literature by analyzing post-pandemic tourist behavior in Latin America, an underexplored context in existing research on sustainable and adventure tourism. The findings offer theoretical contributions to the field of adventure tourism and practical recommendations for destination managers seeking to enhance their competitiveness and visitor retention in the post-pandemic context.